ANALISIS STRUKTUR DAN PROSEDUR PENGELOLAAN KEUANGAN PADA PT. GARDA PAKSI NUSANTARA - Kartika Legistari; Resmi Ranti Rosalina (Jurnal Ekbis (Ekonomi & Bisnis), 2025)
This study aims to analyze the structure and financial management procedures of PT. Garda Paksi Nusantara, a security service company with complex and labor-intensive operational activities. A descriptive qualitative approach was employed, supported by interviews, observations, and documentation as data collection techniques. The findings indicate that the company’s financial organizational structure has not been formally established, resulting in unclear division of duties, authority, and authorization flows. Financial procedures such as cash receipts, cash disbursements, procurement, transaction recording, and financial reporting do not yet have standardized written SOPs, causing inconsistencies and potential inefficiencies in implementation. Internal control is also weak due to the absence of functional segregation and suboptimal verification and authorization processes. Moreover, the company still relies on manual bookkeeping, which affects data accuracy and slows down administrative processing. The study concludes that PT. Garda Paksi Nusantara needs to improve its financial organizational structure, strengthen SOPs, enhance internal control mechanisms, and adopt integrated digital accounting systems to achieve more effective, efficient, and accountable financial management. Keywords: financial management, organizational structure, financial SOP, internal control